2023
DOI: 10.1093/molbev/msad012
|View full text |Cite
|
Sign up to set email alerts
|

Interactomics: Dozens of Viruses, Co-evolving With Humans, Including the Influenza A Virus, may Actively Distort Human Aging

Abstract: Some viruses (e.g. HIV-1, SARS-CoV-2) have been experimentally proposed to accelerate features of human ageing and of cellular senescence. These observations, along with evolutionary considerations on viral fitness, raised the more general puzzling hypothesis that, beyond documented sources in human genetics, ageing in our species may also depend on virally-encoded interactions distorting our ageing to the benefits of diverse viruses. Accordingly, we designed systematic network-based analyses of the human and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 153 publications
0
5
0
Order By: Relevance
“…There is evidence that senescence contributes to the pathophysiology of respiratory viral infections, 34 and a recent report has observed that viruses may convergently contribute to the evolution of human aging. 35 Thus, we assumed that all patients suffered from viral infections in a similar proportion and all of them were recruited previous COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that senescence contributes to the pathophysiology of respiratory viral infections, 34 and a recent report has observed that viruses may convergently contribute to the evolution of human aging. 35 Thus, we assumed that all patients suffered from viral infections in a similar proportion and all of them were recruited previous COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, the importance of senescence in acute inflammatory conditions such as respiratory viral infections has been less approached until the COVID‐19 outbreak, as it has been mainly addressed in chronic infections. There is evidence that senescence contributes to the pathophysiology of respiratory viral infections, 34 and a recent report has observed that viruses may convergently contribute to the evolution of human aging 35 . Thus, we assumed that all patients suffered from viral infections in a similar proportion and all of them were recruited previous COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-and eukaryotes alike are furthermore prone to viral infections (La Scola et al, 2003) and over the course of eukaryotic evolution, multicellular organisms J Physiol 602.11 have further coevolved with a varying infectious and symbiotic viriome and microbiome that has consistently contributed to organismal health and disease (Moelling, 2020;Roossinck, 2015;Villarreal & Ryan, 2019;Witzany, 2020;Gontier & Sukhoverkhov 2023), and, as recently shown, organismal ageing (Teulière et al, 2023).…”
Section: Situating Physiology Within the Flower Of Evolutionmentioning
confidence: 99%
“…Moreover, cellular senescence has also been described as an anti-viral mechanism [ 77 , 78 , 79 , 80 , 81 , 82 ]; thus, it is unsurprising that many viruses, including SARS-CoV-2, have been shown to directly induce cellular senescence [ 80 , 83 , 84 ]. Recently, a systematic network-based analysis of the human and viral protein interactomes produced a list of the top viral candidates predicted to influence human aging; among these, the influenza A virus (subtype H1N1) has emerged as the leading candidate, primarily due to its genetic, encoded potential to interact with cellular senescence [ 85 ].…”
Section: Alteration Of Microbiome and Viromementioning
confidence: 99%